2021
DOI: 10.1002/rcs.2285
|View full text |Cite
|
Sign up to set email alerts
|

An improved method for assessing the technical accuracy of optical tracking systems for orthopaedic surgical navigation

Abstract: Background Optical tracking systems (OTSs) are essential components of many modern computer assisted orthopaedic surgery (CAOS) systems but patient movement is often neglected in the evaluation of the accuracy. The aim of this study was to develop a representative test to assess the accuracy of OTSs including patient movement and demonstrate the effect of pointer design and OTS choice. Method A mobile phantom with dynamic reference base (DRB) attached was designed and constructed. The point registration truene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
(100 reference statements)
0
8
0
Order By: Relevance
“…For the correct interpretation of the results of this study, it is important to stress that the camera system used was an order of magnitude more accurate compared to commercially applied systems for computer‐assisted orthopaedic surgery 22 . The 2σ confidence interval of the commonly used Polaris P4, Polaris Spectra passive and Stryker camera is 0.86 mm, 0.35 and 0.15 mm, respectively, compared to 0.09 mm for the Krypton 610 used in this study 20–22 . While the reported errors in the study can largely be linked to the registration process itself, in clinical practice, an additional error related to the tracking system could be expected.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…For the correct interpretation of the results of this study, it is important to stress that the camera system used was an order of magnitude more accurate compared to commercially applied systems for computer‐assisted orthopaedic surgery 22 . The 2σ confidence interval of the commonly used Polaris P4, Polaris Spectra passive and Stryker camera is 0.86 mm, 0.35 and 0.15 mm, respectively, compared to 0.09 mm for the Krypton 610 used in this study 20–22 . While the reported errors in the study can largely be linked to the registration process itself, in clinical practice, an additional error related to the tracking system could be expected.…”
Section: Discussionmentioning
confidence: 83%
“…For the correct interpretation of the results of this study, it is important to stress that the camera system used was an order of magnitude more accurate compared to used in this study. [20][21][22] While the reported errors in the study can largely be linked to the registration process itself, in clinical practice, an additional error related to the tracking system could be expected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical results in the present study indicated a stable implant accuracy under robotic assistance across a reasonable range of implant length and diameter. The high level of accuracy observed is dependent upon the convergence of three sets of factors: (i) the trueness of the tracking system of the robot (its tracking system, fiducial technology, and geometric design of the markers) (Herregodts et al, 2021); (ii) the registration process that allows the alignment of the digital and physical anatomy of the region of interest (Simpson et al, 2013); (iii) the ability of the visual control loop of the robot to compensate for patient movements (Dudek et al, 2022). Besides these technical aspects embedded in the design of the tested cobot, the skills of the surgeon to effectively co‐operate with the robot remain essential and so is the ability of the patient to stay still while the robotic drilling is performed.…”
Section: Discussionmentioning
confidence: 99%